2005
DOI: 10.1128/jvi.79.16.10788-10795.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Cytomegalovirus M33 Is Necessary and Sufficient in Virus-Induced Vascular Smooth Muscle Cell Migration

Abstract: Mouse cytomegalovirus (MCMV) encodes two potential seven-transmembrane-spanning proteins with homologies to cellular chemokine receptors, M33 and M78. While these virus-encoded chemokine receptors are necessary for the in vivo pathogenesis of MCMV, the function of these proteins is unknown. Since vascular smooth muscle cell (SMC) migration is of critical importance for the development of atherosclerosis and other vascular diseases, the ability of M33 to promote SMC motility was assessed. Similar to human CMV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…The resulting SMC accumulation in the vessel intima leads to neointimal hyperplasia and vessel narrowing. MCMV and RCMV induce SMC migration that is mediated by virally encoded chemokine receptors M33 and R33, respectively [62,65]. Furthermore, infection with a recombinant strain of RCMV containing an insertional deletion of R33 significantly increases the time to CR, and slows the kinetics of TVS in the rat heart transplant model suggesting that this viral chemokine receptor plays an important role in RCMV acceleration of CR [65].…”
Section: Mechanisms Of CMV Accelerated Tvs and Chronic Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting SMC accumulation in the vessel intima leads to neointimal hyperplasia and vessel narrowing. MCMV and RCMV induce SMC migration that is mediated by virally encoded chemokine receptors M33 and R33, respectively [62,65]. Furthermore, infection with a recombinant strain of RCMV containing an insertional deletion of R33 significantly increases the time to CR, and slows the kinetics of TVS in the rat heart transplant model suggesting that this viral chemokine receptor plays an important role in RCMV acceleration of CR [65].…”
Section: Mechanisms Of CMV Accelerated Tvs and Chronic Rejectionmentioning
confidence: 99%
“…In addition, CMV modifies a number of cellular functions that then mediate viral spread, persistence and immune evasion. For instance, CMV also induces cellular factors involved in angiogenesis and wound repair processes including adhesion molecules (ICAM-1, VCAM-1, VAP-1, and E-selectin,) and growth factors and receptors (TGF-β, PDGF-AA, VEGF, and PDGFR) [37,52,[55][56][57][58][59][60][61][62][63][64][65]. In addition, increased matrix metalloproteinase (MMP)-2 activity is observed in HCMV infected cells in conjunction with a reduction in matrix gene expression, resulting in a malleability to SMC migration, an alteration in vessel remodeling which promotes a vasculopathy [49,50].…”
Section: Mechanisms Of CMV Accelerated Tvs and Chronic Rejectionmentioning
confidence: 99%
“…For example, M33 and R33 couple to G q/11 to stimulate InsP accumulation and NF-κB activity in an agonist-independent manner (Gruijthuijsen et al, 2002;Sherrill and Miller, 2006;Waldhoer et al, 2002). Furthermore, M33, like US28, also stimulates smooth muscle cell migration which is suggested to be mediated through Rac-1, a Rho-like G protein (Melnychuk et al, 2005;Streblow et al, 2003). In vivo studies assessing their biological significance indicate that deletion of either M33 or R33 from their respective viral genomes decreases viral replication in animal models of infection.…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…Thus, similar to regulation of mGluR1 as described above, GRK2 can regulate viral GPCR signaling in both a phosphorylation-dependent and phosphorylation-independent manner. Preliminary studies from our lab also suggest that M33 can recruit β-arrestin, thus potentially enabling M33 to activate the NF-κB and ERK pathways in a G protein independent fashion (Melnychuk et al, 2005;Waldhoer et al, 2002). Future experiments aimed at defining the mechanism by which M33 induces NF-κB and ERK activation and the potential roles that these signaling pathways play in M33 function in vivo will be important as we continue to define the biological function of M33 in terms of viral pathogenesis.…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…Whilst UL33 has been shown to constitutively activate the PLC/IP pathway, predominantly via Gαq, signalling through CREB, it has presented no induction on NF-κB activation in fibroblasts Waldhoer et al, 2002). Although the effect of UL33 on cellular migration is unknown, studies with the MCMV UL33 counterpart (M33) showed that it was necessary and sufficient to promote SMC migration (Melnychuk et al, 2005). No studies have been made evaluating the effects on the signalling properties of UL33 when the GPCR DRY-motif is disrupted.…”
Section: Chapter 3 -Hcmv Vgpcr Effects Upon Human Cell Types 31 Intrmentioning
confidence: 99%